The Equilibrium Real Exchange Rate in a Commodity Exporting Country : Algeria's Experience - Koranchelian, Taline (IMF Working Papers; Working Paper, 2005)
Drawing on the existing literature, I estimate a long-run equilibrium real exchange rate path for Algeria. I find that the Balassa-Samuelson effect together with real oil prices explain the long-run evolution of the equilibrium real exchange rate in Algeria. The half-life of the deviation of the real exchange rate from the estimated equilibrium level is about nine months, similar to that in other commodity-exporting countries. The general conclusions are that: (i) there is a time-varying long-run equilibrium exchange rate in Algeria as in other commodity-exporting countries; and (ii) the real effective exchange rate of the Algerian dinar at end-2003 was broadly in line with this equilibrium.